Unregulated Gatekeepers: Oversight Independence Gaps in Indonesia's Sustainable Sukuk Framework - Albana, Muhammad Abdur Rosyid; Heradhyaksa, Bagas; Pamesti, Pas Ingrid; Bawana, Tate Agape (TAWAZUN: Journal of Sharia Economic Law, 2026)
The issuance of sustainable sukuk has emerged as a critical mechanism for financing projects aligned with environmental and social objectives. In Indonesia, the Financial Services Authority (OJK) regulates such instruments through POJK No. 18 of 2023, which mandates independent external reviewers to assess sustainability frameworks and ensure transparency. However, this study demonstrates that Articles 13 and 46 of the regulation lack detailed provisions regarding reviewer independence, competence, and accountability, particularly in relation to accreditation standards, selection procedures, and oversight mechanisms. Employing a normative legal method with statutory and conceptual approaches, the analysis reveals significant legal and institutional gaps that compromise the integrity of sustainability assessments. These gaps increase greenwashing risks due to insufficient oversight mechanisms and the absence of accreditation standards for ESG reviewers. Comparative analysis with international standards, including the ICMA Green Bond Principles, ASEAN Green Bond Standards, and the EU Green Taxonomy, confirms that Indonesia's current provisions are inadequate, particularly in requiring accredited reviewers, mandatory conflict-of-interest disclosure, and post-issuance verification. This study proposes three main recommendations: regulatory revision to specify reviewer qualifications, responsibilities, and conflict-of-interest rules; establishment of an independent oversight unit within OJK; and adoption of accreditation systems aligned with international ESG assurance frameworks. Theoretically, this research contributes to integrating oversight independence theory into Islamic capital market regulation by demonstrating that structural separation and institutional safeguards are essential to prevent conflicts of interest—thereby complementing agency theory and governance assurance frameworks.